2022
DOI: 10.3389/fncel.2022.849160
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation Enables Temperature Robustness and Coupling Between Fast and Slow Oscillator Circuits

Abstract: Acute temperature changes can disrupt neuronal activity and coordination with severe consequences for animal behavior and survival. Nonetheless, two rhythmic neuronal circuits in the crustacean stomatogastric ganglion (STG) and their coordination are maintained across a broad temperature range. However, it remains unclear how this temperature robustness is achieved. Here, we dissociate temperature effects on the rhythm generating circuits from those on upstream ganglia. We demonstrate that heat-activated facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 66 publications
(153 reference statements)
1
14
0
Order By: Relevance
“…Given the leech's ability to maintain neural firing across significant environmental temperature changes, owing presumably to similar compensation mechanisms to those described in other organisms (Robertson and Money, 2012;Städele et al, 2015;Städele and Stein, 2022), we were initially surprised that artificial temperature increases as low as 2 °C could cause the dramatic modulation of neural activity we observed (Collins et al, 2021). One key difference between our heating modalities and those employed in most studies examining temperature compensation is the spatial gradient of the temperature increase.…”
Section: Thermal Effects On Neural Activity At Moderate Temperatures:...mentioning
confidence: 86%
“…Given the leech's ability to maintain neural firing across significant environmental temperature changes, owing presumably to similar compensation mechanisms to those described in other organisms (Robertson and Money, 2012;Städele et al, 2015;Städele and Stein, 2022), we were initially surprised that artificial temperature increases as low as 2 °C could cause the dramatic modulation of neural activity we observed (Collins et al, 2021). One key difference between our heating modalities and those employed in most studies examining temperature compensation is the spatial gradient of the temperature increase.…”
Section: Thermal Effects On Neural Activity At Moderate Temperatures:...mentioning
confidence: 86%
“…A number of studies have found that signaling molecules and feedback modulation play a role in maintaining circuit function even though the molecular kinetics of all cellular components are altered due to changes in temperature ( Zhurov and Brezina, 2005 ; Hamilton et al, 2007 ; Biron et al, 2008 ; Tang et al, 2010 ; Thuma et al, 2013 ; Städele et al, 2015 ; Haddad and Marder, 2018 ; Takeishi et al, 2020 ; Städele and Stein, 2022 ). As such, we were particularly interested in examining the role of feedback in determining the crash temperature in this neuromuscular system.…”
Section: Discussionmentioning
confidence: 99%
“…Because each ion channel type can be differently affected by changes in temperature, predicting how temperature change will affect even a single neuron is not simple (Caplan et al, 2014;O'Leary and Marder, 2016;Alonso and Marder, 2020). These predictions are even more difficult to understand when extrapolating to neural circuits, as synaptic (Tang et al, 2010;Rinberg et al, 2013;Soofi et al, 2014;Städele et al, 2015;O'Leary and Marder, 2016;Alonso and Marder, 2020;Powell et al, 2021;Ratliff et al, 2021;Städele and Stein, 2022) and muscle physiology (Harri and Florey, 1977;Foldes et al, 1978;Rutkove, 2001;Racinais and Oksa, 2010;Thuma et al, 2013;Kushinsky et al, 2019; this paper) are also affected. Some processes of temperature compensation in the neural circuits of poikilotherms have been revealed (Harri and Florey, 1977;Foldes et al, 1978;Rutkove, 2001;Racinais and Oksa, 2010;Kushinsky et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations